Exploring how internet memes influence brand coolness perceptions: utilitarian versus hedonic cosmetic brands - Aguiar, Marta Rodrigues (2021)
Nowadays, brands are increasingly acknowledging the advantages of incorporating social media into their marketing strategies as a tool to create and establish relationships with their consumers. One of the most efficient ways to communicate with them is through the use of visual content, being that Internet Memes are a popular choice due to their ease of creation, humorous basis and fast-spreading capabilities on the Internet. One other topic which has been under study in marketing, and trendy in social media, is Brand Coolness. Among other things, Brand Coolness allows brands to sell more, and increase or decrease their online image, loyalty and love. This dissertation suggests that using Internet Memes in brands’ social media pages can influence the perceptions of Brand Coolness and proposes to understand the ‘if’ and the ‘how’, in the cosmetic industry context, and between utilitarian and hedonic brands. Through two surveys, one to assess the most utilitarian and the most hedonic cosmetic brand, and another with two questionnaires to answer to the research questions, the results show that although Internet Memes do influence the perceptions of Brand Coolness, it is only to an extent, and not always in a positive way as it might depend on many factors among them: the intended target, the context in which the Internet Meme is communicated, the subjectivity of humour, the type of brand, and the type of meme. Additionally, a person's age or knowledge of what an Internet Meme is, do not change their perceptions of Brand Coolness.